True pseudo-random number generation using chaotic maps - Chong, Wei Zhen (2015)
In this paper, a new algorithm for generating True Pseudo-Random Number Generator (TPRNG) is proposed. This TPRNG uses chaos theory in dynamic systems that are highly sensitive to changes in initial conditions. The proposed algorithm uses a modified version of the logistic map to generate large sequence of pseudo-random numbers. The performance of the TPRNG is evaluated through exploratory data analysis and several statistical tests from the DIEHARD test suite. The results were promising as they suggest that the numbers have a good distribution and are highly random and independent for a wide range of parameters. Further tests were conducted to compare the TPNG against other existing generators. The analysis showed that the TPRNG is truly more random than common generators used. It can be concluded that the TPRNG can generate a large amount of usable random numbers that are suitable for simulations and other scientific computing applications.